RETRACTED: The Use of AI to Analyze Social Media Attacks for Predictive Analytics - Temitope Samson Adekunle; Oluwaseyi Omotayo Alabi; Morolake Oladayo Lawrence; Godwin Nse Ebong; Grace Oluwamayowa Ajiboye; Temitope Abiodun Bamisaye (Universitas Dian Nuswantoro, 2024)
This article has been retracted at the request of the Editor-in-Chief. The journal was alerted to issues within this article, including significant overlap in content, methodology, and visual materials with another previously published article: